2012
DOI: 10.1177/0895904812453997
|View full text |Cite
|
Sign up to set email alerts
|

Special Education & School Choice

Abstract: This article begins to unpack the complex effects of the policies of both the small schools and choice on students with special needs. Drawing on qualitative data collected throughout the 2008-2009 academic year and a range of quantitative data from New York City's public high schools, the author shows that while small schools and choice are intended to expand schooling options for all, students with special needs often find that when entering the public high school choice process, their selection set is narro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Some prior research found that charter school administrators did not respond to parents’ requests for information if the parent signaled that their child might have more significant needs (Bergman & McFarlin, 2020), thus passively dissuading them from applying. In qualitative studies of school choice in New York City, administrators explicitly told parents of SWD that the services their child needed were not available at their school (Jennings, 2010; Jessen, 2013). Other times administrators and recruitment materials suggested that students not fitting a specific profile would be unsuccessful at their school (Jabbar, 2016; Jessen, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some prior research found that charter school administrators did not respond to parents’ requests for information if the parent signaled that their child might have more significant needs (Bergman & McFarlin, 2020), thus passively dissuading them from applying. In qualitative studies of school choice in New York City, administrators explicitly told parents of SWD that the services their child needed were not available at their school (Jennings, 2010; Jessen, 2013). Other times administrators and recruitment materials suggested that students not fitting a specific profile would be unsuccessful at their school (Jabbar, 2016; Jessen, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In qualitative studies of school choice in New York City, administrators explicitly told parents of SWD that the services their child needed were not available at their school (Jennings, 2010; Jessen, 2013). Other times administrators and recruitment materials suggested that students not fitting a specific profile would be unsuccessful at their school (Jabbar, 2016; Jessen, 2013). Parents of children with more substantial support needs are unlikely to choose a school that explicitly states, or implicitly suggests, they cannot provide more intensive special education services, although under IDEA all schools must provide the services on a student’s IEP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an analysis of market-oriented schools in both England and the United States, West et al (2006) conclude that both skimming and cropping appear to occur when choice and selection are involved. Several studies have found that charter schools are significantly less likely to serve students with disabilities relative to traditional schools (Dudley-Marling & Baker, 2012; Frankenberg et al, 2010; Jessen, 2013; Miron et al, 2010). Bergman and McFarlin (2018) conducted an audit experiment of over 6,000 public schools.…”
Section: Charter School Impact On Traditional Schoolsmentioning
confidence: 99%
“…They may also choose not to act on their desire for interracial/ethnic contact (and better resources) if they anticipate racial/ethnic bias in disciplinary practices, ability classification, and academic tracking in predominantly White schools (see Edwards, 2016; Elder et al, 2021). On the flipside of this dynamic, unfair overidentification of marginalized minority students for mild disabilities (see Skiba et al, 2008) can narrow parents’ choices and motivate them to compromise on various preferences for special education services (Jessen, 2012). In relation to this, they may be less satisfied with the schools in terms of their children’s learning and development.…”
Section: Compromise Among Preferences and Its Relationship With Satis...mentioning
confidence: 99%